1989
DOI: 10.1177/002224378902600309
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Price, Brand Name, and Store Name on Buyers’ Perceptions of Product Quality: An Integrative Review

Abstract: The authors integrate previous research that has investigated experimentally the influence of price, brand name, and/or store name on buyers’ evaluations of product quality. The meta-analysis suggests that, for consumer products, the relationships between price and perceived quality and between brand name and perceived quality are positive and statistically significant. However, the positive effect of store name on perceived quality is small and not statistically significant. Further, the type of experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
524
1
16

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(575 citation statements)
references
References 10 publications
27
524
1
16
Order By: Relevance
“…This is reflected in folk wisdom like "you get what you pay for" or in the use of a "expensive=good heuristic" (Cialdini 2001). In a meta-analysis of 36 studies, a positive relation between price and perceived quality was confirmed (Rao and Monroe 1989). This relation was moderately large (r=.34, η 2 =.12); it was stronger for withinsubjects designs and when the price range of products was larger, i.e., when comparability was easier.…”
Section: Price and Product Quality From The Consumers' Perspectivementioning
confidence: 80%
“…This is reflected in folk wisdom like "you get what you pay for" or in the use of a "expensive=good heuristic" (Cialdini 2001). In a meta-analysis of 36 studies, a positive relation between price and perceived quality was confirmed (Rao and Monroe 1989). This relation was moderately large (r=.34, η 2 =.12); it was stronger for withinsubjects designs and when the price range of products was larger, i.e., when comparability was easier.…”
Section: Price and Product Quality From The Consumers' Perspectivementioning
confidence: 80%
“…Conversely, on encountering negative information about an unfamiliar brand, consumers tend to respond less positively, primarily, because they have no pro-attitudinal information about that brand stored in memory and therefore evaluate the brand solely on the basis of the current crisis information. Rao and Monroe (1989) suggest that a greater likelihood exists for consumers to use extrinsic cues (such as COO information) in the assessment of product quality when they lack intrinsic cues as a result of their low familiarity with a given brand. Consequently, unfamiliar brands inspire more instances of negative bias.…”
Section: The Brand Familiarity Effect and Consumers' Attributions Of mentioning
confidence: 99%
“…Consequently, unfamiliar brands inspire more instances of negative bias. Rao and Monroe (1989) also suggest that as brand familiarity increases, consumers reduce their reliance on extrinsic cues and increase their reliance on intrinsic cues when evaluating brands. Thus, with respect to consumers' assessments of blame, the influence of the COO image becomes more powerful in the case of an unfamiliar brand.…”
Section: The Brand Familiarity Effect and Consumers' Attributions Of mentioning
confidence: 99%
“…Caves and Greene (1996) found a strong positive relationship between price and objective quality for frequently purchased product categories that are convenience goods. Rao and Monroe (1989) argued that a strong positive relationship exists for lower priced, frequently purchased product categories, but that the relationship is not well documented for other categories. 1 There are models of new product introduction and consumer learning in which either a low introductory price (Tirole 1992, page 111) or an inefficiently high introductory price (Bagwell and Riordan 1991) can signal high quality.…”
Section: Past Prices As Signals Of Qualitymentioning
confidence: 99%